2018
DOI: 10.1039/c8pp00070k
|View full text |Cite
|
Sign up to set email alerts
|

β-Diketone derivatives: influence of the chelating group on the photophysical and mechanofluorochromic properties

Abstract: A diphenyl-boron β-diketonate complex was synthesized. Its photophysical properties were studied in solution and in the solid-state, and compared to those of its parent diketone and the corresponding difluoro-boron complex. TD-DFT calculations show that the molecular orbitals involved in the first Franck-Condon transition are very different for the three compounds studied. The difluoro-boron complex is strongly fluorescent in solution, and remains fluorescent in the solid-state. The free diketone turns to be v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The difluoroboron-complex showed mechanofluorochromic responses whereas diphenyl-boron complexes did not show any change in fluorescence upon grinding. 45 Boron-β-diketonates were also investigated as emitters in organic light emitting devices. Sasabe and co-workers studied the OLED properties of a boron-β-diketonate ( 28 ) along with a carbazole derivative which showed an external quantum efficiency ( η ext ) of 10%.…”
Section: Oo-chelate B–o Coordinated Boron Compoundsmentioning
confidence: 99%
“…The difluoroboron-complex showed mechanofluorochromic responses whereas diphenyl-boron complexes did not show any change in fluorescence upon grinding. 45 Boron-β-diketonates were also investigated as emitters in organic light emitting devices. Sasabe and co-workers studied the OLED properties of a boron-β-diketonate ( 28 ) along with a carbazole derivative which showed an external quantum efficiency ( η ext ) of 10%.…”
Section: Oo-chelate B–o Coordinated Boron Compoundsmentioning
confidence: 99%
“…X-ray diffraction data for cyclo-(Phe-Leu-Leu-Leu-Ile) was collected by using a VENTURE PHOTON100 CMOS Bruker diffractometer with Micro-focus IuS source Cu Kα radiation. Crystal was mounted on a CryoLoop (Hampton Research) with Paratone-N (Hampton Research) as cryoprotectant and then flashfrozen in a nitrogen-gas stream at 100 K 64 . The temperature of the crystal was maintained at the selected value by means of an N-Helix cooling device to within an accuracy of ± 1 K. The data were corrected for Lorentz polarization, and absorption effects.…”
Section: Largementioning
confidence: 99%
“…24,25 In addition, solid state luminescence studies showed that many BDK compounds present mechanochromic properties, their emission wavelength being correlated to their solid structure. [26][27][28][29][30][31][32][33][34][35][36][37] BDK compounds, in solid state, were also applied for the detection of volatile amines because these latter can interact with difluoroboron moiety, lowering their acceptor character, leading to blue shifted emission and increase of fluorescence quantum yields. [38][39][40] The development of synthetic methods producing unsymmetrical β-diketone compounds can give access to push pull chromophores i.e.…”
Section: Introductionmentioning
confidence: 99%